Atividade antibacteriana, antifúngica e antioxidante de óleos essenciais - Luchesi, Luana Aline (2017)
The growing use of medicinal plants and essential oils in order to prevent and carrie the diseases treatment, based on the antibacterial, antifungal and antioxidant properties is that the aim of this work, whichs ought to identify the composition and antioxidant activity of some essential oils as Lavandula angustifolia, Pogostemon cablin, Rosmarinus officinalis, Thymus vulgaris, Hedyosmun brasiliense, Psidium guajava, Baccharis dracunculifolia and Schinus terebinthifolius, as well as evaluate the antibacterial potential in vitro against Staphylococcus aureus; Salmonella enteretidis; Escherichia coli e Pseudomonas aeruginosa and antifungal activity in vitro againt Fusarium graminearum. The oils and chromatographies were obtained by hydrodistillation through external partnerships. While the antifungal activity of Baccharis dracunculifolia and Pogostemon cablin oils laying out a mycelial disc of F. graminearum. The scavenging activity of 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical. As a result It was obtained the constitutions of essential oils mainly monoterpenes with 32.5 % of camphor in the Rosmarinus officinalis oil, 47 % of thymol in Thymus vulgaris, 31.5% of patchoulol in Pogostemon cablin; and esters with 40.1% of lanalin acetate in the Lavandula angustifolia oil. In the native plants oils the composition was basically of sesquiterpenes. Such as 17.58% of cis trans nerolidolin the Baccharis dracunculifolia oil; 31.6% of germacrene B in the lemon balm; 16.1% α-selinene in the Psidium guajava oil and 18.6% of α-bergamotene in the Schinus terebinthifolius.. The antibacterial activity of Thymus vulgaris oil has shown the most effective results, with minimal inhibitory concentration (MIC) and minimum bacterial concentration (MBC) of0.195 e 1.56 µL.mL-1 against S. aureus; and 0.195 e 50 µL.mL-1respectively for S. enteritidis; and for E. coli, the MIC was 0,390 µL.mL-1and MBC 0.780 µL.mL-1 and for P. aeruginosa 0.780 and 12.5 µL.mL- 1.The antifungal activities were determined against F. graminearum with Pogostemon cablin (8.0 μL.mL-1) during the period of 96h, It has inhibited 80.0% of the fungus. The antioxidant activity of the Pogostemon cablin essential oil was higher than the others with 12.08 µmol trolox/mL-1 radical scavenging activity. Based on this study, It is suggested that oils as Lavandula angustifólia, Thymus vulgaris, Rosmarinus officinalis, Baccharis dracunculifolia, Psidium guajava and Schinus terebinthifolius, can be used against infections caused by S. aureus, E. coli, S. enteritidis and more closely by P. aeruginosa. Also it was found out that Pogostemon cablin oil may serve as an antifungal agent against the phytopathogen F. graminearum. Moreover, the thyme oil can play an important antioxidant activity.